Endosperm structure and Glycemic Index of Japonica Italian rice varieties - Haxhari, Filip; Savorani, Francesco; Rondanelli, Mariangela; Cantaluppi, Enrico; Campanini, Luigi; Magnani, Edoardo; Simonelli, Cinzia; Gavoci, Gentian; Chiadò, Alessandro; Sozzi, Mattia; Cavallini, Nicola; Chiodoni, Angelica; et al. (Frontiers in Plant Science, 2024)
Considering that rice is the most important staple food for a large part of the world's population and given the growing number of diabetic consumers, individuating and developing low Glycemic Index (GI) varieties, without neglecting grain quality, represents a main goal for genetic improvement. 25 Italian rice genotypes were thus characterized calculating their GI “in vivo”. Furthermore, they were studied, together with other 29 Italian and non-Italian genotypes, to evaluate grain inner structure through Field Emission Scanning Electron Microscopy (FESEM) technique. A large variability was observed in GI values (49 to 92 with respect to glucose), as well as in endosperm morphological features. According to the percentage of porosity is possible to distinguish approximately among rice varieties having a crystalline grain (< 1.7%), those intended for the preparation of risotto (> 5%), and a third group having intermediate characteristics. Waxy rice varieties were not united by a certain porosity level, but they shared a low starch granules eccentricity. With reference to morphological features, rice varieties with low GI (<55) seem to be characterized by large starch granules and low porosity values. Our data testify the wide variability of Italian rice cultivation giving interesting information for future breeding programs, finding that the structure of the endosperm can be regarded as a specific characteristic of each variety.